Effectiveness of Print and Audiovisual Media in Breast Cancer Education to High-School Students - Wardhani, Amanda Carissa; Sari, Sri Yusnita Irda; Badudu, Dharmayanti Francisca (Althea Medical Journal, 2017)
Background: Breast cancer education could be a non-formal education to achieve a proper understanding about early detection of breast cancer. Optimal results need right methods and instruments. Recently, technology development can be implemented to support the non-formal education process. The purpose of this study was to determine the effectiveness between print and audiovisual media in health education on prevention and early detection of breast cancer.Methods: It was a quasi-experimental study, comparing two intervention and one control groups, which was carried out from August to November 2013. The population was senior high school students in Jatinangor subdistrict West Java, Indonesia. The sample was taken by cluster sampling method; each group consisted of 120 female students. Students from Sekolah Menengah Atas Negeri Jatinangor were given printed media, students from Sekolah Menengah Kejuruan Padjadjaran were given audiovisual media and students from Pesantren Al Maâsoem as control group were not given any intervention. The knowledge of respondents was measured with pre-test and post-test questioner. Mean scores of knowledge were further analyzed by paired and independent t-test.Results: The average of pre-test between intervention and control groups were similar (8.125, 8.725 and 8.450, respectively). The result showed that the average scores of post-test increased compared to pre-test both in the printÂ  and audiovisual media group (p=0.001).Conclusions: Print and audiovisual media can increase the knowledge of respondents on prevention and early detection of breast cancer. However, audiovisual media is more effective as a tool for health education especially among teenagers.